Antibiotic resistance of Staphylococcus aureus associated with subclinical and clinical mastitis in Uruguay during an eight-year period - de los Santos, Rosario I.; Zunino, Pablo M.; Gil, Andrés D.; Laport, Adolfo; Hirigoyen, Darío J. (Austral Journal of Veterinary Sciences, 2017)
Records of in vitro susceptibility tests performed between 2008 and 2015 were retrospectively reviewed in order to evaluate the dynamic profiles of possible changes in antimicrobial resistance of Staphylococcus aureus isolated from milk samples of cows with subclinical mastitis from 12 different Uruguayan Provinces. The results of 1,631 isolates tested by disk diffusion technique for susceptibility to penicillin and erythromycin were analysed. The possible tendency or changes in the behaviour of this pathogen against penicillin and erythromycin in the 8 year period was evaluated using the chi-square tests for trend and the homogeneity. The highest rate of resistance was observed for penicillin (36.9% in 2010), while erythromycin showed a resistance rate significantly lower (5.7% in 2015). The test for trend showed a significant trend towards decreased resistance to penicillin, whereas for erythromycin an increased resistance trend was observed. The determination of the scope of the problem is essential for the formulation and monitoring of effective response to anti-microbial resistance (AMR). Antibiotic assessment in Uruguay is now being reviewed with the objective of limiting antibiotics prescription to professionals trained to select a successful therapy, choosing the appropriated drug and treatment duration according each situation. To generate knowledge on the magnitude and tendency of the AMR problem using country-specific information must be a priority.